DC distribution network to enable solar village part I - Chin, Sok Fang (2019)
DC microgrid has become more popular over the years with advancements in technology. With existing AC power grid and more DC loads in the market, it is advantageous to directly connect the DC loads to the DC microgrid, thereby reducing the need for AC/DC conversions. Compared to single bus distribution system, multiple-bus (or multi-bus) distribution system allows DC loads of different voltages to be directly connected to the DC microgrid. This project investigates the maximum constant power load at each bus using stability analysis to determine the maximum power available from the converters. Small signal analysis is employed to analyze the stability of the multi-bus DC microgrid.